8p23.1 deletion: Look out for left ventricular hypertrabeculation and not only congenital heart diseases. Single‐center experience and literature revision. Issue 3 (13th December 2021) - Cicenia, Marianna; Alesi, Viola; Orlando, Valeria; Magliozzi, Monia; Di Tommaso, Silvia; Iodice, Francesca G.; Pompei, Emanuela; Toscano, Alessandra; Digilio, Maria C.; Drago, Fabrizio; Novelli, Antonio; Baban, Anwar
Abstract: Deletions involving the distal portion of the short arm of chromosome 8(8p23.1) show a high phenotypic variability. Congenital heart diseases (CHD) are often described. GATA4 when mutated or deleted is reported to be involved in cardiac morphogenesis. Only twice, left ventricular non compaction (LVNC) was reported in literature in association with 8p23.1 deletion. The present cohort includes five new patients with 8p23.1 deletions including GATA4. The spectrum of CHD is variable. Moreover, in four patients, LV hypertrabeculation was detected and in the fifth LVNC was recognized. Literature revision identified 45 patients with 8p23.1 deletions (encompassing GATA4) and heart involvement. It included wide spectrum of CHD including: heterotaxy spectrum 7/45 (15, 6%), atrioventricular canal 14/45 (balanced 3/45 including two of them with hypoplastic aortic arch; unbalanced 4/45, Fallot—AVC 1/45, partial AVC 3/45, unspecified 3/45), predominant major left heart lesions included 2/45 (4, 4%): interrupted aortic arch and hypoplastic left heart syndrome. Left ventricular hypertrabeculation might be potentially underestimated in patients with 8p23.1 deletion. These might suggest the importance of including microarray analysis in this group of patients. Moreover, 8p23.1 microdeletion or GATA4 variants can be considered in heterotaxy genetic panels.